Pacing the phasing of leg and arm movements in breaststroke swimming to minimize intra-cyclic velocity fluctuations - van Houwelingen, Josje (PLoS One, 2017)
In swimming propelling efficiency is partly determined by intra-cyclic velocity fluctuations. The higher these fluctuations are at a given average swimming velocity, the less efficient is the propulsion. This study explored whether the leg-arm coordination (i.e. phase relation ϕ) within the breaststroke cycle can be influenced with acoustic pacing, and whether the so induced changes are accompanied by changes in intra-cyclic velocity fluctuations. Twenty-six participants were asked to couple their propulsive leg and arm movements to a double-tone metronome beat and to keep their average swimming velocity constant over trials. The metronome imposed five different phase relations ϕ(i) (90, 135, 180, 225 and 270°) of leg-arm coordination. Swimmers adjusted their technique under the influence of the metronome, but failed to comply to the velocity requirement for ϕ = 90 and 135°. For imposed ϕ = 180, 225 and 270°, the intra-cyclic velocity fluctuations increased with increasing ϕ, while average swimming velocity did not differ. This suggests that acoustic pacing may be used to adjust ϕ and thereby performance of breaststroke swimming given the dependence of propelling efficiency on ϕ.